Fiducial marker placement for stereotactic body radiation therapy via convex probe endobronchial ultrasound: a case series and review of literature - Seides, Benjamin J. (J Thorac Dis, 2018)
Convex probe endobronchial ultrasound (CP-EBUS) and stereotactic body radiotherapy (SBRT) are valuable tools in the diagnosis, staging, and treatment of thoracic malignancies. With widespread clinical adoption, novel uses of CP-EBUS beyond mediastinal diagnosis and staging continue to be discovered. SBRT is an attractive treatment strategy in early-stage lung cancer and oligo-metastatic disease of the chest when a surgical approach is either not feasible or desirable. Accurate application of SBRT is aided by the placement of radio-opaque fiducial markers (FM) to compensate for respiratory cycle movements. We describe eight patients with central thoracic lesions, either known or suspected to be malignant, who underwent EBUS bronchoscopy with lesion sampling and successful intralesional placement of modified FM via our technique, review the existing literature on this topic, and discuss the nuances of coding and billing aspects of FM placement.